2013
DOI: 10.1038/srep01629
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine Prevents NF-κB Nuclear Translocation And Ameliorates Acute Intestinal Inflammation

Abstract: Oxymatrine is a traditional Chinese herbal product that exhibits anti-inflammatory effects in models of heart, brain and liver injury. We investigated the impact of oxymatrine in an acute model of intestinal injury and inflammation. Oxymatrine significantly decreased LPS-induced NF-κB-driven luciferase activity, correlating with diminished induction of Cxcl2, Tnfα and Il6 mRNA expression in rat IEC-6 and murine BMDC. Although oxymatrine decreased LPS-induced p65 nuclear translocation and binding to the Cxcl2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 46 publications
2
63
0
Order By: Relevance
“…Activation of NF-κB with concomitant over expression of TNF-α and IL-1β in acute colon inflammation in animal studies and intestinal specimens from patients with crohn's disease has been previously reported (Franchimont et al, 2004;Guzman et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 87%
“…Activation of NF-κB with concomitant over expression of TNF-α and IL-1β in acute colon inflammation in animal studies and intestinal specimens from patients with crohn's disease has been previously reported (Franchimont et al, 2004;Guzman et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 87%
“…OMT has been reported to have various medicinal qualities, including antiviral [7], antifibrotic [8], anti-inflammatory [9], and antiarrhythmic [10] effects, and is also widely used in China for the treatment of chronic hepatitis B. Previous in vitro and in vivo studies have shown that OMT inhibits cell proliferation and induces apoptosis in various types of cancers [1115].…”
Section: Introductionmentioning
confidence: 99%
“…Oxymatrine (molecular formula, C 15 H 24 N 2 O 2 ; see Figure 1) is one of the key components extracted from Sophora flavescens, a leguminous plant grown in China, Japan, and some European countries, 10 and has attracted much attention because of its low toxicity and side effects. Extensive research over the past decades have revealed various important pharmacological activities of oxymatrine under in vitro and in vivo conditions, including anti-inflammation, immunoregulatory, antihepatitis virus infection, antihepatic fibrosis, antianaphylaxis, and other immune regulation.…”
Section: Introductionmentioning
confidence: 99%